Estudo do efeito de mistura de petróleos na determinação da acidez, do teor de enxofre, do ponto de fluidez, da viscosidade e do grau API dos blends obtidos - Tozzi, Fabrício Carlos (2015)
Brazil is not a major producer of light oils, and moreover, Brazilian refineries do not yet processed heavy oils, then an alternative would be the mixture of light oils, or lighter characteristics with heavy oil, which would lead to formation of a "new oil" with relatively light feature. The name of this process is blending and these mixtures are called blends. When preparing a blend, there is the formation of a "new" oil with different characteristics when compared to the original matrix (oil or blend), so it is important to assess the impact of this mixture in the new physicochemical properties produced. In this work, four oils were used, two offshore oil designated A and B (API Gravity = 26.4 to 18.3) and two onshore designated C and D (API Gravity = 12.2 and 19.6, respectively ) are classified as the most heavy, which were used to produce 68 blends. These were analyzed and the new values for the physico-chemical properties of the blends as TAN, total sulfur, pour point, viscosity and API gravity were evaluated and compared to the original oils. Among the blends produced 68, 13 blends exhibited both an improvement in values for TAN, all S, pour point and API gravity. It is worth noting that two blends (B30 and B34 named) had the best results for the TAN, the total S, kinematic viscosity and API gravity. Since the chemical composition used in preparing these blends were differentiated, there is also a need to check the influence of the concentration of oils A, B, C and D results from these blends. You can check an important contribution of the oil in these results. Therefore, we conclude that when there is a large production of light oils, the mixing of heavy oils facilitates the formation of mixtures with relatively lighter oil characteristics, optimizing thus the stages of production, processing and refining.